2013
DOI: 10.1007/s00264-013-1929-y
|View full text |Cite
|
Sign up to set email alerts
|

Constraint choice in revision knee arthroplasty

Abstract: Purpose Along with the increase in primary total knee arthroplasty, there has been an increase in the number of revisions. The aim of this study was to propose a selection algorithm for the knee revision constraint according to the state of ligaments and to the bone defects Anderson Orthopaedic Research Institute Classification [AORI] classification. The hypothesis was that this algorithm would facilitate the appropriate choice of prosthesis constraint, thus providing stable components and a good long-term sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 25 publications
2
51
1
Order By: Relevance
“…In relation to the demographic characteristics of our study population, the average ages of our groups are somewhat higher than primary knee arthroplasty studies reported by Vasso et al [10], Deshmukh et al [11], Lachiewicz and Fatalyn [12], Anderson et al [13], Asif and Choon [18], Kane et al [21], Robinson [22], García-Crespo et al [21], Thelu et al [24], Abbas and Gunn [25] and Nakama et al [26] in the literature. Our patients had average ages of 70.5 years and nearly 61 % were older than 65 years.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…In relation to the demographic characteristics of our study population, the average ages of our groups are somewhat higher than primary knee arthroplasty studies reported by Vasso et al [10], Deshmukh et al [11], Lachiewicz and Fatalyn [12], Anderson et al [13], Asif and Choon [18], Kane et al [21], Robinson [22], García-Crespo et al [21], Thelu et al [24], Abbas and Gunn [25] and Nakama et al [26] in the literature. Our patients had average ages of 70.5 years and nearly 61 % were older than 65 years.…”
Section: Discussioncontrasting
confidence: 49%
“…Hinge prosthesis as primary implant is restricted to treat tumoural pathologies. Similar algorithms have been published recently to facilitate the appropriate choice of prosthesis constraint in knee replacement [10].…”
Section: Introductionmentioning
confidence: 99%
“…2 CCK systems are generally indicated in patients with intermediate ligamentous insufficiency and moderate bone loss, whereas RH systems are required in the presence of complete disruption of the ligaments and/or severe bone loss. 45 …”
Section: Constraintmentioning
confidence: 99%
“…34 Prostheses implanted at revision included PS, CCK and RHK. Constraint choice for the revision prosthesis depended on the state of the ligaments and on the severity of bone loss according to AORI (Anderson Orthopaedic Research Institute) classification.…”
Section: Discussionmentioning
confidence: 99%